PERNIKAHAN DINI DALAM TINJAUAN HUKUM ISLAM DAN PSIKOLOGI: EARLY MARRIAGE IN A REVIEW OF ISLAMIC LAW AND PSYCHOLOGY - Habibi, Ahmad (Mitsaqan Ghalizan, 2022)
This paper examines how early marriage is a phenomenon that is currently common in Indonesia. The analysis carried out in this paper is to examine the perspective of Islamic law and the psychological perspective of early marriage. The purpose of marriage is according to Islamic teachings and the goodness of the parties directly interested, and on the basis of "maslahah mursalah". Psychology sees that early marriage is not just an age limit for humans. Because early marriage is more accurately described as young marriage. This reason is more related on issues of non-physical development, both biological development and psychological development (emotional, cognitive and social)